Sodobna dvojezična leksikografija - Krek, Simon (Jezik in slovstvo, 2003)
The article deals with some practical issues in modern biblingual lexicography, Its themes include language resources necessary for the work of a modern lexicographer, basic methodology of lexicographic work, computer format of the dictionary and the final result, a dictionary database. Among the language resources, the existing dictionaries are highlighted together with language corpora as indispensable source of language data for modern lexicography. Methodology is presented by using some practical examples from the Slovenian-English language pair. As the standard computer format of modern dictionaries, SGML/XML format is pointed up as the one allowing to control the structure of the dictionary and because of its software independence. The final result of the lexicographer's work is the computer database in SGML/XML format that contains information of various levels, with the printed dictionary only one of them.
Keywords: Slovene; slovenščina; leksikografija; lexicography; Corpus linguistics; korpusno jezikoslovje; bilingualism; dvojezičnost